Evaluation of Student Satisfaction with the Use of ChatGPT in the Selected Chapters Course using the SUS Method - Aryo Bimo Putra Pratama; Suprih Widodo; Ulva Elviani (FKIP - Universitas Riau, 2026)
The use of artificial intelligence technologies such as ChatGPT has increasingly been integrated into student learning activities in higher education, including the Selected Capita course in the Information Systems and Technology Education Study Program (PSTI). However, student satisfaction and user experience with this technology have not been sufficiently evaluated using standardized instruments. This study aims to evaluate the usability and student satisfaction toward the use of ChatGPT in the Selected Capita course using the System Usability Scale (SUS). This study employed a quantitative survey approach, with the sample determined using the Slovin formula, resulting in 60 PSTI students who had taken the course as respondents. Data were collected through an online questionnaire distributed via Google Forms and analyzed using Microsoft Excel. The preliminary survey showed that 68.3% of students utilized ChatGPT in their learning activities. The SUS analysis produced an average score of 78.2, which falls into the Good category (Grade B+), indicating that ChatGPT is easy to use, intuitive, and provides a positive user experience. In conclusion, ChatGPT demonstrates good usability and is positively received by students, although improvements are still needed in usage limitations, response accuracy, and answer consistency.